Internet and the commercial digital libraries - García-Marco, Francisco-Javier (Anuario ThinkEPI, 2010)
The emergence, concept and characteristics of commercial digital libraries are analyzed. Special attention is given to their potential impact on the cultural and industrial ecosystem of which libraries are an important part, but which faces challenges.
Keywords: Digital libraries; Commercial libraries; Book selling; Trends.